What is Discovery Learning Can Grow Critical Thinking Skills? - Sukartiningsih, Sri; Sarmini, Sarmini; M., Jacky (The Indonesian Journal of Social Studies, 2019)
Critical thinking is one of the skills that must be taught to students as an effect of globalization and the demands of skilled workers in the period of the Industrial Revolution 4.0. Various learning methods, models and strategies are developed to meet these objectives. One of them is the use of the Independent Learning Activity Unit (UKBM) teaching materials in learning to achieve the learning goals of students' critical thinking skills. The focus of this study is to describe students 'responses to the use of UKBM Sociology based on discovery learning to foster students' critical thinking skills. This research is a quantitative descriptive study with percentage techniques. Data is collected through questionnaires, observation and interviews. While the analysis is carried out through four stages, namely data collection, data reduction, data presentation and conclusion drawing. This study shows several conclusions: 1) UKBM Sociology is effectively used in classroom learning to foster students' critical thinking skills; 2) the most prominent assessment is the aspect of student interest in the attractive UKBM design; 3) the assessment is less prominent in the aspect of the discovery learning approach in learning because it requires a long time and the seriousness of the teacher and students. This paper recommends using another learning model at UKBM to foster critical thinking skills.